KAJIAN FILOSOFIS HINDU PADA BARONG LANDUNG DI DESA PAKRAMAN SEMBUNG, MENGWI, BADUNG - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Barong Landung when with religious beliefs will be the last resort if humans encounter problems that cannot be solved with common sense, such as pest attacks on plants, infectious diseases in the community and so on. The magical and religious aspects of Barong Landung are presented as a manifestation of God in ritual ceremonies that are applied to expel disturbing bhuta kala. The form of Barong Landung in Sembung Village, Mengwi District, Badung Regency consists of: (1) historical form; the form of barong landung related to the history of the ancient Balinese king, namely King Balingkang who was married to a Chinese named Kang Ching We who was cursed by Dewi Danu which caused the king and his consort to turn into statues of men and women who were often nicknamed barong landung; (2) the shape is seen from the way it is made (anthromorphic motifs (human motifs), mythological story themes, smooth tapel types, symbolism expressions, complete faces); (3) form based on aesthetics (using clothing and accessories). The functions of Barong Landung in Sembung Village, Mengwi District, Badung Regency are: a function as a sacred art (religious magic), and a function as a syncretization of Chinese culture and Balinese culture. The Philosophical Meanings of Barong Landung in Sembung Village, Mengwi District, Badung Regency, namely: The meaning of the essence of human life, the spirit of facing life, the meaning of aesthetics, the meaning of rwa bhineda.